Palladium-catalysed cascade cyclisation of alkynyl silanes and studies towards rubriflordilactone A - Cordonnier, M; Marie-Caroline Cordonnier (2011)
In this work, a new methodology for the synthesis of a number of silylated bicyclic dienes has been reported. These bicyclic dienes allowed access to a variety of enones and phenols in 2 further steps. The stabilities and reactivities of different dialkylisopropoxy silanes have been evaluated,revealing relative instability of the dimethylisopropoxy silyl group towards chromatography. When using the analogous diethylisopropoxy silyl group instead, the products showed greater stability towards chromatography, however a higher temperature was necessary to oxidise the more sterically hindered silyl group to the desired hydroxyl moiety. A powerful cascade cyclisation for the synthesis of the CDE-core of rubriflordilactone A was then demonstrated and was successfully used for the synthesis of two systems, 284 and 333. The phenolic oxygen has been successfully installed by oxidation of a dialkylisopropoxy silane. The synthesis of these ring systems provides a solid foundation for the completion of the total synthesis of rubriflordilactone A. Finally the synthesis of suitable diynes 405 for the synthesis of the acyclic precursor of the cyclisation has been achieved. The stabilities of theses silanes towards a range of reaction have been demonstrated.